Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40168-018-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-mediated gut microbiome alterations influence sexual dimorphism in metabolic syndrome in mice

Abstract: BackgroundUnderstanding the mechanism of the sexual dimorphism in susceptibility to obesity and metabolic syndrome (MS) is important for the development of effective interventions for MS.ResultsHere we show that gut microbiome mediates the preventive effect of estrogen (17β-estradiol) on metabolic endotoxemia (ME) and low-grade chronic inflammation (LGCI), the underlying causes of MS and chronic diseases. The characteristic profiles of gut microbiome observed in female and 17β-estradiol-treated male and ovarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
168
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 98 publications
(146 reference statements)
6
168
1
1
Order By: Relevance
“…However, we saw no significant differences in alpha or beta diversity across treatment groups and the community composition and size, inferred from a lack of differences in cecal weights, was similar, even at finer taxonomic scales. The lack of differences, particularly between OVX and SHAM groups was unexpected, particularly as OVX was accompanied by increased visceral adiposity and several previous studies have reported OVX-associated microbial shifts [52]. However, there are multiple environmental factors that can influence the microbiota, such as diet, age, and time post-OVX, that may account for differences between our study and previous reports.…”
Section: Discussioncontrasting
confidence: 68%
“…However, we saw no significant differences in alpha or beta diversity across treatment groups and the community composition and size, inferred from a lack of differences in cecal weights, was similar, even at finer taxonomic scales. The lack of differences, particularly between OVX and SHAM groups was unexpected, particularly as OVX was accompanied by increased visceral adiposity and several previous studies have reported OVX-associated microbial shifts [52]. However, there are multiple environmental factors that can influence the microbiota, such as diet, age, and time post-OVX, that may account for differences between our study and previous reports.…”
Section: Discussioncontrasting
confidence: 68%
“…E2 treatment may protect from HFD-induced metabolic disorders through blocking LPS activation [112]. Additionally, E2 upregulates intestinal alkaline phosphatase, a protein with protective role in the gut epithelium through attenuation of proinflammatory signals in the intestine [43]. Taken together with the present findings, estrogens can alter gut microbiota through multiple direct and indirect mechanisms to protect from metabolic disorders.…”
Section: Discussionmentioning
confidence: 62%
“…were negatively associated. The current and previous studies suggest that various gut microbial communities collectively exert E2-mediated protection against HFD-induced weight gain [38, 43].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations